DFT and AFIR study on the copper(i)-catalyzed mechanism of 5-enamine-trisubstituted-1, 2, 3-triazole synthesis via C–N cross-coupling and the origin of ring-opening of 2H-azirines. Issue 5 (13th January 2021) - Yu, Fan; Zhou, Zhaoman; Song, Jiajia; Zhao, Yanying
Abstract : The Cu(i )-catalyzed mechanism of 5-enamined-functionalized fully substituted 1, 2, 3-triazole synthesis was rationalized by interrupted copper(i )-catalyzed terminal alkynes and organic azides click reaction (CuAAC). Abstract : Understanding the synthesis mechanism of substituted 1, 2, 3-triazoles is an important and state-of-the-art research area of contemporary copper(i )-catalyzed terminal alkyne and organic azide click reaction (CuAAC), which has invoked increasing close collaborations between experiment and theory including copper catalyzed interrupted click reaction. In this study, the mechanism of Cu(i )-catalyzed 5-enamine-functionalized fully substituted 1, 2, 3-triazole synthesis was rationalized via density functional theory (DFT) and multicomponent artificial force-induced reaction (MC-AFIR) methods. The reasonable reaction route consists of (a) di-copper catalyzed ring-opening of 2 H -azirines, (b) alkyne hydrogen atom transfer, (c) [3 + 2] ring cycloaddition, and (d) C–N bond formation through reductive elimination. The MC-AFIR method was used for the systematic determination of transition states for the C/N–Cu bond formation, C–N bond coupling and crossing points between singlet and triplet states. Our survey on the prereactant complexes suggested that the dicopper-catalyzed 2 H -azirine ring-opening and alkyne hydrogen activation are both thermodynamically feasible via a singlet/triplet crossing point. This explains why Et3 N is critical for alkyne hydrogen transfer (HT) before the [3 + 2] cycloaddition reaction, and the C–N cross-coupling product instead of the click product (byproduct). Our DFT results indicate that the transmetalation process is the rate determination step along the triplet state potential energy surface. This study provides important mechanistic insights for the interrupted CuAAC reaction to form 5-enamine-fully-substituted-1, 2, 3-triazoles. Further insight prediction interprets that solvent and extra strong ligand coordination play a certain role in competitive reactions.